Spectrum analysis of current in single-phase half-bridge inverter in domain of two variables - Korotyeyev, I.Ye. (Технічна електродинаміка, 2015)
The object of this paper is a spectrum analysis of a load current in a single-phase half-bridge inverter with PWM. The analysis is based on an extension of differential equations with one variable of time to partial differential equations with two time variables. The partial differential equation is solved with the use of the two dimensional Laplace transform. The obtained solution is described in the form of a double Fourier series. This result is transformed into such form that permits description as a spectrum in the domain of two discrete variables. Метою статті є гармонійний аналіз струму навантаження в однофазному напівмостовому інверторі з ШІМ. Аналіз базується на розширенні диференціальних рівнянь, що описуються однією змінною часу до рівнянь у частинних похідних, описуваних двома змінними часу. Диференціальне рівняння у частинних похідних вирішується за допомогою двовимірного перетворення Лапласа. Отримане рішення представляється у формі подвійного ряду Фур'є. Отриманий результат перетворюється на форму, яка дозволяє опис у вигляді спектра в просторі двох дискретних змінних. Целью статьи является гармонический анализ тока нагрузки в однофазном полумостовом инверторе с ШИМ. Анализ основывается на расширении дифференциальных уравнений, описываемых одной переменой времени, до уравнений в частных производных, описываемых двумя переменными времени. Дифференциальное уравнение в частных производных решается с помощью двумерного преобразования Лапласа. Полученное решение представляется в форме двойного ряда Фурье. Полученный результат преобразуется в форму, которая позволяет описание в виде спектра в пространстве двух дискретных переменных.